Isolation of Indole-3-Acetic Acid (IAA) Producing Endophytic Bacteria from Shallot (Allium cepa L.) Root - Nofiyanti, Safinatus Sabrina; Rahayu, Yuni Sri (LenteraBio : Berkala Ilmiah Biologi, 2023)
Research to isolate IAA-producing endophytic bacteria from various plants is necessary because each plant can show different types and abilities of endophytic bacteria to produce IAA. The shallot plant is a commodity that requires increased productivity because the amount is still lacking compared to the amount consumed. Therefore, this study aimed to isolate and characterize the endophytic bacteria from shallot (Allium cepa L.) root, then to determine its ability to produce IAA qualitatively and quantitatively. The characterization consists of colony morphology, gram properties, cell shape, and cell arrangement. Testing the ability of bacteria to synthesize IAA was carried out qualitatively using the Salkowski method and quantitatively using the spectrophotometric method. Based on the research results, twelve bacterial isolates were found, including isolates A61, A62, A63, A51, B61, B51, B52, B53, C51, C52, C53, and C61. The results showed that all isolates were able to produce IAA with an average concentration of 15,180 ppm (A63); 13.256 ppm (A62); 10.228 ppm (A51); 9.952 ppm (B51); 9.241 ppm (B61); 8.662 ppm (C51); 7.326 ppm (B52); 6,703 ppm (C52); 6,272 ppm (C61); 6.158 ppm (A61); 6.005 ppm (C53); and 5.018 ppm (B53). Onion root endophytic bacterial isolates were able to produce IAA optimally on the third day of incubation, which ranged from 6.006 - 23.391 ppm. The endophytic bacterial isolate with the highest concentration (A63) has the potential to be used as a growth promoter for shallot plants so that productivity can increase.